EVALUATION OF THE IMPLEMENTATION OF CHARACTER EARLY CHILHOOD EDUCATION - Suwardi Suwardi (CAKRAWALA DINI: JURNAL PENDIDIKAN ANAK USIA DINI, 2018)
Abstract:. Character education in particular are still enforced in early childhood institutions, while at the next level of education is still limited in Pancasila and Citizenship Education. On the other hand we are still very often obtain information about the behavior of learners in education levels after early childhood institutions are often brawls (the character of tolerance and peaceful), cheating during exams (characters honesty), and a number of other behaviors. It is one of the things that underlie this research; is necessary to evaluate the implementation of character education at early childhood. Research evaluation of the implementation of character education on early childhood aimed evaluated well as provide recommendations on the implementation of character education early childhood. The method used is descriptive qualitative evaluation model developed by Stuflbeam CIPP (Context, Input, Process, and Product), which phase of the evaluation context and input..Object that implemented in research in this study is the early childhood institution.Keyword: Evaluation, Character Education Abstrak: Pendidikan karakter khususnya masih ditegakkan di lembaga pendidikan anak usia dini, sedangkan pada tingkat pendidikan berikutnya masih terbatas di Pancasila dan Pendidikan Kewarganegaraan. Di sisi lain kita masih sangat sering memperoleh informasi tentang perilaku peserta didik di tingkat pendidikan setelah lembaga anak usia dini sering bertengkar (karakter toleransi dan damai), menyontek saat ujian (karakter kejujuran), dan sejumlah perilaku lainnya. Ini adalah salah satu hal yang mendasari penelitian ini; diperlukan untuk mengevaluasi pelaksanaan pendidikan karakter di AUD. Evaluasi penelitian terhadap pelaksanaan pendidikan karakter AUD bertujuan mengavaluasi dengan baik serta memberikan rekomendasi pada pelaksanaan pendidikan karakter AUD. Metode yang digunakan adalah model evaluasi kualitatif deskriptif yang dikembangkan oleh Stuflbeam CIPP (Konteks, Input, Proses, dan Produk), yang fase dari konteks evaluasi dan input. Obyek yang diimplementasikan dalam penelitian dalam penelitian ini adalah lembaga AUD.Kata Kunci: Evaluasi, Pendidikan karakter  Character education in particular are still enforced in early childhood institutions, while at the next level of education is still limited in Pancasila and Citizenship Education. On the other hand we are still very often obtain information about the behavior of learners in education levels after early childhood institutions are often brawls (the character of tolerance and peaceful), cheating during exams (characters honesty), and a number of other behaviors. It is one of the things that underlie this research; is necessary to evaluate the implementation of character education at AUD. Research evaluation of the implementation of character education AUD aimedmengavaluasi well as provide recommendations on the implementation of character education AUD. The method used is descriptive qualitative evaluation model developed byStuflbeam CIPP (Context, Input, Process, and Product), which phase of the evaluation context and input..Objek implemented in research in this study is the institution AUD.Keyword : Evaluation, Character Education